Evaluation of the remineralisation of the demineralized enamel surrounding orthodontic brackets using the nano hydroxyapatite: An original study - Sahithi Samineni; Bhupendra S Rathore; Nitika Rohilla; Praveen K Varma; Kumar B Niwlikar; Sankar N Sarma (Wolters Kluwer Medknow Publications, 2023)
Introduction: The orthodontic appliances have been known to accelerate enamel loss due to various reasons. Since there are few studies supporting the role of the nano-HAP in the mineralization of the demineralized tooth surfaces, the current study compared nano-HAP's capacity to remineralize the demineralized enamel layer surrounding braces at various concentration levels. Materials and Procedures: This investigation involved 60 healthy permanent premolars that had just been excised. All specimens had 3M-Unitek brackets glued to their buccal surfaces. The samples were artificially demineralized and divided into three groups. The control group, Toothpaste ApaCare, and ApaCareTM varnish. Before and after remineralization, selected samples from each group were analyzed using a "Scanning Electron Microscope (SEM)" and evaluated using "Energy Dispersive X-Ray Analysis (EDAX)." Spectrometer and profilometer were used for the study of surface and the color. Statistics were used to analyze the outcomes. The threshold for significance was fixed at 0.05. Results: After remineralization by nano-HAP, there was a significant rise (P < 0.001) in both calcium and phosphorus levels. This was picked up by EDAX, and SEM verified it. When compared to the control group, the nano-HAP application greatly improved the color measurements in the study groups (P < 0.001), and it also resulted in a significant decrease in surface roughness (P < 0.001). Conclusion: Our study's results showed that nano-HAP could be successful in restoring demineralized enamel around brackets, reducing the surface roughness and color of the enamel surface.